Regulated input price, vertical separation, and leadership in free entry markets - Toshihiro Matsumura; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2012)
We examine incentives of bottleneck facility holders to manipulate access charge accounting in free entry downstream markets. We consider the situation wherein one firm holds an upstream bottleneck facility and new entrants use it at the regulated price (access fee) to provide final products. The bottleneck facility holder affects the regulated input price. We investigate how vertical separation affects the incentive for manipulation and the resulting input price. We find that the results depend on whether the incumbent is the Stackelberg leader in the product market. If the incumbent cannot take leadership in the product market and faces Cournot competition, vertical separation reduces the incentive for manipulation and the resulting input price. The opposite result is derived when the incumbent can take leadership in the product market.
Keywords: L51; L13; 330; network industry; access charge; manipulation of accounting; regulation; Netzregulierung; Markteintritt; Regulierung; Bottleneck; Duopol; Theorie